Targeting human CALR‐mutated MPN progenitors with a neoepitope‐directed monoclonal antibody. (14th February 2022) - Tvorogov, Denis; Thompson‐Peach, Chloe A L; Foßelteder, Johannes; Dottore, Mara; Stomski, Frank; Onnesha, Suraiya A; Lim, Kelly; Moretti, Paul A B; Pitson, Stuart M; Ross, David M; Reinisch, Andreas; Thomas, Daniel; et al.
Abstract: Calreticulin (CALR) is recurrently mutated in myelofibrosis via a frameshift that removes an endoplasmic reticulum retention signal, creating a neoepitope potentially targetable by immunotherapeutic approaches. We developed a specific rat monoclonal IgG2α antibody, 4D7, directed against the common sequence encoded by both insertion and deletion mutations. 4D7 selectively bound to cells co‐expressing mutant CALR and thrombopoietin receptor (TpoR) and blocked JAK‐STAT signalling, TPO‐independent proliferation and megakaryocyte differentiation of mutant CALR myelofibrosis progenitors by disrupting the binding of CALR dimers to TpoR. Importantly, 4D7 inhibited proliferation of patient samples with both insertion and deletion CALR mutations but not JAK2 V617F and prolonged survival in xenografted bone marrow models of mutant CALR‐dependent myeloproliferation. Together, our data demonstrate a novel therapeutic approach to target a problematic disease driven by a recurrent somatic mutation that would normally be considered undruggable. Synopsis: CALR is recurrently mutated in myelofibrosis, creating a surface‐exposed neoepitope that activates the thrombopoietin receptor. A monoclonal antibody (4D7) with mutation‐specific efficacy in CALR mutant progenitors disrupts the receptor‐CALR complex and inhibits proliferation. 4D7 specifically blocks mutant CALR‐dependent proliferation and TPO‐independent megakaryocyte differentiation. Neoepitope targeting is a feasible and attractive strategy to overcome ruxolitinib‐persistence. Neoepitope targeting disrupts CALR oligomerisation with MPL and subsequent signal transduction. 4D7 inhibits proliferation of patient samples with CALR mutations and prolongs survival in xenograft models. Abstract : CALR is recurrently mutated in myelofibrosis, creating a surface‐exposed neoepitope that activates the thrombopoietin receptor. A monoclonal antibody (4D7) with mutation‐specific efficacy in CALR mutant progenitors disrupts the receptor‐CALR complex and inhibits proliferation.